Proposing a New Method for Procurement System in Universiti Teknologi PETRONAS - Nur Dalila binti Radzali @ Razali, Nur Dalila (Universiti Teknologi Petronas, 2012)
The main objective of this research is to find new method to enhance the procurement system in Universiti Teknologi PETRONAS (UTP) by using tools that can assist in enhancing the procurement system. The problem with current conduct is that, there is no computerized system that can help in decision making to raise a Purchase Requisition (PR) and can help track and manage inventory movement, which cost in time and effort due to physical counting and leads to high human error and operational tasks ineffi ciency. This research encompasses the Inventory Management relation to Procurement process, which utilizes the web application e-Inventory Management Information System (eIMIS). The project looks at the related works by researchers from various scope of study, which includes inventory management concepts, the importance of tracking the stock age of an inventory and tracking the inventory level and how inventory helps in managing procurement. It focus more on the consumables inventory in Universiti Teknologi PETRONAS labs, developed using ASP.Net language and having Microsoft Access 2007 as the database. This paper also touches on the system flow, mechanism and tools used to develop and use the web application. Two surveys were conducted to gather information on the user acceptance towards the system and on the web application general look and feel, which uses the System Usability Scale standards to know the level of the usability of the elMIS. The result shows that the system is perceived as convenience and useful in completing daily tasks of the users and the SUS is 82.25%o, which is high in usability.